Reply to Stafford's (2022) comment on "Seaweed ecosystems may not mitigate CO2 emissions" by Gallagher et al. (2022). (19th May 2022) - Gallagher, John Barry; Shelamoff, Victor
Abstract: The comment qualitatively suggests that seaweed ecosystems are global carbon sinks. This was in contradiction to the article that showed that seaweed ecosystems are on average measurably carbon sources within the canopy. Furthermore, this was amplified by the remineralization of a large fraction of exported seaweed production, as estimated from published parameters. It appeared that the comments' conclusion was mistaken from two standpoints. First, a view that the article did not consider the impact of the phytoplanktonic assemblage on the seaweed ecosystems' global sequestration rate. This had been previously calculated as likely, not significant. Second, a view that the consumption and subsequent respiration of exported material cannot be included in ecosystems that are generally open to allochthonous organic carbon subsidies. Nevertheless, the comment does raise the importance of a more holistic view in assessing sequestration services. The response expands the article's arguments from different standpoints and consequences to illustrate where the comment has been mistaken, and points out where the article was misread. We also expand on the comments' call for a more holistic approach by being more explicit on what drives both sequestration and mitigation through the extreme circumstances where this could be maximized, including phytoplankton contributions.